Beyond halal in food product: present and future of halalan tayyiban - Md Dahlal, Norazilawati; Ahmad, Fadzila Azni (Society of Interdisciplinary Business Research, 2018)
Contemporary demand for halal products has been increasing globally. The demand is not only from Muslim consumers but also non-Muslims consumers. When the growing trend in applying the halal concept and consuming halal products becomes increasingly universal, then the opportunity for consumers to evaluate prospective halal products would increase. This includes evaluation of the consumer’s safety issues and sustainable health. One of the most discussed consumption issues is food additives. Food additives have become the main ingredient in processed foods as it functions to enhancer to the physical quality of processed foods. However, food additives also have a deleterious effect on human health and this raises an incongruity with the tayyiban concept when implementing a halalan tayyiban diet. Hence, this study intended to re-evaluate the quality of halal processed foods that contain halal food additives from a tayyiban perspective. This study was conducted in two parts. First, it identified the function of food additives and their impact on food products. Second, it analysed the use of halalan tayyiban quality management procedures on halal food products that contained food additives. This qualitative study adopted the content analysis method to systematically verify facts and evidence. The findings showed that most of food products that used food additives had received halal status certification. Although food additives are categorised as halal; hence, from a tayyiban aspect, it is still an issue. The discussions in this study had helped improve the quality of processed halal foods. Lastly, this working paper suggested an appropriate form of certification for halal processed foods that could effectively fulfil the requirement of the halalan tayyiban concept.